Feasibility of hydrogel fiducial markers for in vivo proton range verification using PET. (23rd February 2016) - Cho, Jongmin; Campbell, Patrick; Wang, Min; Alqathami, Mamdooh; Mawlawi, Osama; Kerr, Matthew; Cho, Sang Hyun
Abstract: Biocompatible/biodegradable hydrogel polymers were immersed in 18 O-enriched water and 16 O-water to create 18 O-water hydrogels and 16 O-water hydrogels. In both cases, the hydrogels were made of ~91 wt% water and ~9 wt% polymer. In addition, 5–8 μ m Zn powder was suspended in 16 O-water and 18 O-enriched water and cross-linked with hydrogel polymers to create Zn/ 16 O-water hydrogels (30/70 wt%, ~9 wt% polymer) and Zn/ 18 O-water hydrogels (10/90 wt%), respectively. A block of extra-firm 'wet' tofu (12.3  ×  8.8  ×  4.9 cm, ρ   ≈  1.05 g cm −3 ) immersed in water was injected with Zn/ 16 O-water hydrogels (0.9 ml each) at four different depths using an 18-gauge needle. Similarly, Zn/ 18 O-water hydrogels (0.9 ml) were injected into a second tofu phantom. As a reference, both 16 O-water hydrogels (1.8 ml) and 18 O-water hydrogels (0.9 ml) in Petri dishes were irradiated in a 'dry' environment. The hydrogels in the wet tofu phantoms and dry Petri dishes were scanned via CT and images were used for treatment planning. Then, they were positioned at the proton distal dose fall-off region and irradiated (2 Gy) followed by PET/CT imaging. Notably high PET signals were observed only in 18 O-water hydrogels in the dry environment. The visibility of the Zn/ 16 O-water hydrogels injected into the tofu phantom was outstanding in CT images, but these hydrogels provided no noticeable PET signals. The visibility of the Zn/ 18 O-water hydrogels in the wet tofu were excellent on CT and moderate on PET; however, the PET signals were weaker than those in the dry environment, possibly owing to 18 O-water leaching out. The hydrogel markers studied here could be used to develop universal PET/CT fiducial markers. Their PET visibility (attributed more to activated 18 O-water than Zn) after proton irradiation can be used for proton therapy/range verification. More investigation is needed to slow down the leaching of 18 O-water.